Irregularity Measures for Metal-Organic Networks. (1st August 2020) - Guo, Xuan; Chu, Yu-Ming; Hashmi, Muhammad Khalid; Virk, Abaid Ur Rehman; Li, Jingjng
Abstract : Topological index plays an important role in predicting physicochemical properties of a molecular structure. With the help of the topological index, we can associate a single number with a molecular graph. Drugs and other chemical compounds are frequently demonstrated as different polygonal shapes, trees, graphs, etc. In this paper, we will compute irregularity indices for metal-organic networks.